2011
DOI: 10.1002/mar.20411
|View full text |Cite
|
Sign up to set email alerts
|

Older consumers' Tv home shopping: Loneliness, parasocial interaction, and perceived convenience

Abstract: This study examined factors that affect consumer satisfaction with TV shopping by investigating both convenience-and emotion-related variables. Data were obtained from 295 online surveys with TV home shoppers who were 60 years and older. The structural model revealed (1) a positive effect of lack of shopping mobility on loneliness and perceived convenience of TV shopping, (2) a positive effect of loneliness on parasocial interaction, and (3) positive effects of parasocial interaction and perceived convenience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 70 publications
(107 reference statements)
2
61
0
1
Order By: Relevance
“…Well-being was measured by three items developed by Pavot and Diener [49]; Samaha and Hawi [50]; and Kong, Ding, and Zhao [51]. Social exclusion was measured with four items from Huxley et al [52] and Lim and Kim [53].…”
Section: Methodsmentioning
confidence: 99%
“…Well-being was measured by three items developed by Pavot and Diener [49]; Samaha and Hawi [50]; and Kong, Ding, and Zhao [51]. Social exclusion was measured with four items from Huxley et al [52] and Lim and Kim [53].…”
Section: Methodsmentioning
confidence: 99%
“…Limited research has shown that parasocial relationships with celebrities have a positive effect on consumer attitudes and behaviors related to celebrity endorsement. For instance, Lim and Kim (2011) found that consumers who developed parasocial interactions with TV shopping hosts are likely to have higher levels of shopping satisfaction. Similarly, consumers were found to have positive attitudes toward products (Knoll, Schramm, Schallhorn, & Wynistorf, 2015) and strong intentions to purchase them (Kim, Ko, & Kim, 2015) when the products were endorsed by celebrities with whom consumers had built parasocial relationships.…”
Section: Parasocial Relationshipsmentioning
confidence: 99%
“…Though a large number of studies regarding service convenience have been conducted, previous studies have asserted that convenience is more important among older customers [26,65]. In addition, as individuals are older, they are more likely to rely on the Internet [25] and TV home shopping [26] due to physical immobility. Lim and Kim [26] suggested that TV shopping companies can satisfy older customers with limited shopping mobility by adding convenience benefits [26].…”
Section: Customer Satisfactionmentioning
confidence: 99%